Pd–PdO Nanodomains on Amorphous Ru Metallene Oxide for High‐Performance Multifunctional Electrocatalysis. Issue 12 (7th February 2023) - Do, Viet‐Hung; Prabhu, P; Jose, Vishal; Yoshida, Takefumi; Zhou, Yingtang; Miwa, Hiroko; Kaneko, Takuma; Uruga, Tomoya; Iwasawa, Yasuhiro; Lee, Jong‐Min
Abstract: Developing highly efficient multifunctional electrocatalysts is crucial for future sustainable energy pursuits, but remains a great challenge. Herein, a facile synthetic strategy is used to confine atomically thin Pd–PdO nanodomains to amorphous Ru metallene oxide (RuO2 ). The as‐synthesized electrocatalyst (Pd2 RuOx‐0.5 h) exhibits excellent catalytic activity toward the pH‐universal hydrogen evolution reaction (η10 = 14 mV in 1 m KOH, η10 = 12 mV in 0.5 m H2 SO4, and η10 = 22 mV in 1 m PBS), alkaline oxygen evolution reaction (η10 = 225 mV), and overall water splitting ( E 10 = 1.49 V) with high mass activity and operational stability. Further reduction endows the material (Pd2 RuOx‐2 h) with a promising alkaline oxygen reduction activity, evidenced by high halfway potential, four‐electron selectivity, and excellent poison tolerance. The enhanced catalytic activity is attributed to the rational integration of favorable nanostructures, including 1) the atomically thin nanosheet morphology, 2) the coexisting amorphous and defective crystalline phases, and 3) the multi‐component heterostructural features. These structural factors effectively regulate the material's electronic configuration and the adsorption of intermediates at the active sites for favorable reaction energetics. Abstract : Direct heterostructure engineering on an ultrathin 2D platform of Pd–PdO nanodomains confined on amorphous RuO2 yields excellent catalytic activity toward pH‐universal HER, alkaline oxygen electrochemistry, and overall water splitting. The enhanced multifunctional performance is attributed to the rational integration of novel nanostructures, including atomically thin morphology, coexisting amorphous and defect‐rich crystalline phases, and multicomponent heterostructural features.